2008
DOI: 10.1161/circulationaha.107.744466
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Syndrome and Risk of Development of Atrial Fibrillation

Abstract: Background-The metabolic syndrome consists of a cluster of atherosclerotic risk factors, many of which also have been implicated in the genesis of atrial fibrillation (AF). However, the precise role of the metabolic syndrome in the development of AF is unknown. Methods and Results-This prospective, community-based, observational cohort study was based on an annual health check-up program in Japan. We studied 28 449 participants without baseline AF. We used 2 different criteria for the metabolic syndrome-the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(176 citation statements)
references
References 50 publications
6
163
1
6
Order By: Relevance
“…Prior studies examining risk of atrial fibrillation in relation to diabetes or impaired glucose metabolism have yielded conflicting results. 3,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our results are similar to those reported by several prospective studies, 12,14,18 including the Framingham Heart Study, 14 all of which reported ORs in the range of 1.4 to 1.6. Other studies found an association between higher blood glucose and increased risk of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prior studies examining risk of atrial fibrillation in relation to diabetes or impaired glucose metabolism have yielded conflicting results. 3,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our results are similar to those reported by several prospective studies, 12,14,18 including the Framingham Heart Study, 14 all of which reported ORs in the range of 1.4 to 1.6. Other studies found an association between higher blood glucose and increased risk of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 90%
“…Both findings are associated with heightened risk of atrial fibrillation, 3,7-9 a common and serious arrhythmia that confers significant risks for stroke and death. 10,11 Many epidemiologic studies have examined atrial fibrillation risk in relation to diabetes or elevated blood glucose, with conflicting results: ten studies observed an association, 3,9,[12][13][14][15][16][17][18][19] while nine did not. 11,[20][21][22][23][24][25][26][27] Often, prior studies examined many possible predictive factors and were not designed to evaluate the role of diabetes specifically.…”
Section: Introductionmentioning
confidence: 99%
“…The population with AF will significantly increase in the future with the increasingly aging society 1. In addition to the well‐known risk factors, including hypertension, diabetes mellitus, cardiovascular disease, obesity, metabolic syndrome, and chronic kidney disease, lifestyle characteristics such as alcohol consumption are significantly linked to the incidence and/or prevalence of AF 2, 3, 4, 5. Although catheter ablation (CA) is standard therapy for patients with AF,6, 7, 8 the impact of alcohol consumption on the outcomes of CA has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Aggrecan is one of the major components of cartilage and binds to hyaluronan (HA) and links proteins to form huge aggregates. These aggregates lead to a hydrated gel-like structure of cartilage and resistibility to compression and deformation in joints [9]. Currently, there has been vast research to study factors that promote cartilage repair.…”
Section: Introductionmentioning
confidence: 99%